Aging towards walkable futures: insights from a multidisciplinary workshop held in Barcelona, Spain - Vall-Garcia, Enric; Delgado-Ortiz, Laura; Alcock, Lisa; Coll-Planas, Laura; García-Navarro, José Augusto; Iwarsson, Susanne; Jansà, Josep Maria; Jansen, Carl-Philipp; Koch, Sarah; Schwartz, Simon; Rantakokko, Merja; Sarukhan, Adelaida; et al. (BMC public health, 2025)
Background The aging of the world’s population and the increase in sedentary lifestyles are leading to an increase in walking impairments at older ages. Here, we aimed to comprehensively discuss walking in the context of an aging population; and identify and agree on a list of future research priorities and policy actions. Methods We followed a participatory approach and held a multidisciplinary two‑day workshop on October, 2023 in Barcelona, Spain, with experts in the fields of aging and walking, and participants from the general public. Results A total of 56 national and international participants, from a multidisciplinary background, joined the workshop. They had a median age of 40 years (range 24–83), and 62% were female. Participants discussed the meaning of walking from different perspectives and its change with age and in the presence of diverse mobility‑impairing conditions; the emotional and social components of walking; and the role of the environment in walking. Participants identified unmet needs, research priorities and policy actions related to walking in older ages. Conclusions This two‑day workshop provided a space for professionals and public to comprehensively discuss walking at older ages. Participants highlighted the relevance of a better and more comprehensive assessment of walking; the need to shift focus towards comprehensive health that considers physical, emotional and social aspects as well as ndividuals’ preferences and expectations; and the importance of translating research into action. Future work can draw on the discussions held during this event in a thought‑provoking and hypothesis‑generating way.